Model of Causal Factors of Network Management Capabilities Affecting Market Opportunity and Performance of Community Enterprises - Lalaeng, Chanyaphak; Sumpathanon, Chanita; Boonnual, Chutimant (Journal of Ecohumanism, 2024)
Objectives: Research Model of causal factors of network management capabilities affecting market opportunity and performance of community enterprises. This paper examines to check the consistency of the model. To develop a model of causal factors of network management capabilities affecting market opportunity and performance of community enterprises in this sector. Methods: The population used in this study was a group of small and medium-sized enterprises in the upper southern region of Thailand, a sample of 320 (Wiratchai, 1999). Using the PLS model, a two-stage approach was used for direct path and mediation effect analysis with high-dimensional latent variables. Results: The analysis revealed that both PCBE and CL were statistically significant in relation to NMC. Furthermore, NMC were found to be statistically significant for Market opportunity (MO) and Business performance (BP). However, MO did directly influence BP. Conclusions: In light of these findings, we discuss the theoretical and practical implications, limitations of the study. This study underscores the importance of Perceived changes in the business environment and Creative leadership the indirect pathways through which Network management capabilities contribute to Market opportunity success and Business performance.